Pathogenesis and novel treatment options for non-alcoholic steatohepatitis. (September 2016) - Wong, Vincent Wai-Sun; Chitturi, Shiv; Wong, Grace Lai-Hung; Yu, Jun; Chan, Henry Lik-Yuen; Farrell, Geoffrey C
Summary: Non-alcoholic fatty liver disease affects 20–40% of the population. Its active form, non-alcoholic steatohepatitis (NASH), is characterised by hepatocyte injury, liver inflammation, and progression of fibrosis, and has emerged as one of the most important causes of liver failure and hepatocellular carcinoma. Weight reduction of 10% by dietary restriction and regular exercise is sufficient to reverse NASH in most patients, but in practice this reduction is often not achieved. Available drugs such as vitamin E, pioglitazone, and pentoxifylline have borderline efficacy, but are limited by potential side-effects and toxicities, and do not improve liver fibrosis. However, basic and translational research has improved our understanding of the pathophysiology of NASH, thereby identifying several promising new treatment targets. Several drugs are in phase 2 and 3 development and could enter clinical practice in the near future. In this Review, we discuss the pathogenesis, treatment evaluation, existing therapies, and potential new treatments for NASH.